The effects of thermal manipulation during the late incubation period on hatching traits and production performance in broiler - Fadhel, Ahmed (University of Thi-Qar Journal of agricultural research, 2025)
This study, conducted over 56 days from November 3 to December 29, 2024, examined the effects of thermal manipulation during late incubation on hatching traits, chick quality, and post-hatch performance in Ross 308 broilers. The work began at Almiass’s private hatchery and continued at Sulaymaniyah University’s College of Agricultural Engineering Sciences. The study involved 750 eggs across five groups. Until day 18, all eggs were incubated at 37.5°C with 60–65% humidity. From days 19–21, one control and four thermally manipulated groups continued at 37.5°C and 70–75% humidity, with TM groups exposed to 6-hour daily cycles at varying temperatures (36.5°C, 35.5°C, 38.5°C, and 39.5°C) before returning to the baseline. Key parameters assessed included hatchability, embryonic mortality, chick quality, growth, feed intake, feed conversion ratio, and carcass traits. Higher incubation temperatures—especially 39.5°C—reduced hatch time but negatively affected hatchability and increased late embryonic mortality. Two indicators of chick quality were observed: the chick length was greater in the T0 group compared to the T4 group, while the T4 group exhibited a higher malformation rate than the T0 group. Even though the feed intake of all TM groups was significantly higher than that of the control, the 35.5°C group gained the most body weight after hatching. There were no appreciable changes in either the production index or the cumulative FCR. While the percentages of thighs and wings were the same, the 39.5°C group’s breast output rose. Overall, TM had an impact on a few hatching and performance parameters.